Challenging the ideal strength limit in single-crystalline gold nanoflakes through phase engineering - Tong Zhang; Yuanbiao Tong; Chenxinyu Pan; Jun Pei; Xiaomeng Wang; Tao Liu; Binglun Yin; Pan Wang; Yang Gao; Limin Tong; Wei Yang (Nature Communications)
Abstract Materials usually fracture before reaching their ideal strength limits. Meanwhile, materials with high strength generally have poor ductility, and vice versa. For example, gold with the conventional face-centered cubic (FCC) phase is highly ductile while the yield strength (~102 MPa) is significantly lower than its ideal theoretical limit. Here, through phase engineering, we show that defect-free single-crystalline gold nanoflakes with the hexagonal close-packed (HCP) phase can exhibit a strength of 6.0 GPa, which is beyond the ideal theoretical limit of the conventional FCC counterpart. The lattice structure is thickness-dependent and the FCC-HCP phase transformation happens in the range of 11–13 nm. Suspended-nanoindentations based on atomic force microscopy (AFM) show that the Young’s modulus and tensile strength are also thickness-and phase- dependent. The maximum strength is reached in HCP nanoflakes thinner than 10 nm. First-principles and molecular dynamics (MD) calculations demonstrate that the mechanical properties arise from the unconventional HCP structure as well as the strong surface effect. Our study provides valuable insights into the fabrication of nanometals with extraordinary mechanical properties through phase engineering.